Research advances in the application of vagus nerve electrical stimulation in ischemic stroke - Cheng, Keling; Wang, Zhiyong; Bai, Junhui; Xiong, Jie; Chen, Jianmin; Ni, Jun (Frontiers in Neuroscience, 2022)
Stroke seriously endangers human well-being and brings a severe burden to family and society. Different post-stroke dysfunctions result in an impaired ability to perform activities of daily living. Standard rehabilitative therapies may not meet the requirements for functional improvement after a stroke; thus, alternative approaches need to be proposed. Currently, vagus nerve stimulation (VNS) is clinically applied for the treatment of epilepsy, depression, cluster headache and migraine, while its treatment of various dysfunctions after an ischemic stroke is still in the clinical research stage. Recent studies have confirmed that VNS has neuroprotective effects in animal models of transient and permanent focal cerebral ischemia, and that its combination with rehabilitative training significantly improves upper limb motor dysfunction and dysphagia. In addition, vagus-related anatomical structures and neurotransmitters are closely implicated in memory–cognition enhancement processes, suggesting that VNS is promising as a potential treatment for cognitive dysfunction after an ischemic stroke. In this review, we outline the current status of the application of VNS (invasive and non-invasive) in diverse functional impairments after an ischemic stroke, followed by an in-depth discussion of the underlying mechanisms of its mediated neuroprotective effects. Finally, we summarize the current clinical implementation challenges and adverse events of VNS and put forward some suggestions for its future research direction. Research on VNS for ischemic stroke has reached a critical stage. Determining how to achieve the clinical transformation of this technology safely and effectively is important, and more animal and clinical studies are needed to clarify its therapeutic mechanism.